Evolving Patterns of Anxiety and Depression Among Pharmacy Students: A One-Year Observational Study - Dewi Susanti Atmaja; Yuwindry, Iwan (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Mental health issues, particularly anxiety and depression, are increasingly concerning for university students. Pharmacy students are especially vulnerable to stress owing to high academic demands. This study is one of the first longitudinal analyses exploring the evolution of anxiety and depression symptoms among Indonesian pharmacy students. Objective: To observe the longitudinal patterns of depression and anxiety symptoms among pharmacy students using the Patient Health Questionnaire 9 (PHQ-9) and Generalized Anxiety Disorder 7 (GAD-7) over an academic year. Methods: This prospective cohort study involved 106 first-year pharmacy students (undergraduate and professional programs). Depression and anxiety symptoms were measured using the PHQ-9 and GAD-7 instruments at two time points: the beginning and the end of the academic year. Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank test. Results: The mean GAD-7 score slightly increased from 9.15 (SD=3.29) to 9.45 (SD=3.47), while the PHQ-9 score increased from 10.81 (SD=4.37) to 11.47 (SD=4.56). Wilcoxon tests showed that the increase in anxiety was not statistically significant (p=0.036), whereas the paired t-test indicated that the increase in depression was not statistically significant (p=0.079). However, a higher severity category was observed for depressive symptoms. Conclusion: Although changes in anxiety and depression scores were not statistically significant, a trend toward worsening depressive symptoms was observed during the academic year. These findings highlight the importance of continuous mental health monitoring and early supportive intervention among pharmacy students.